Evaluation of Abortion Measures in Government Regulation No. 28 of 2024 on The Right to Life of the Fetus From a Human Rights Perspective - Florencia Desiree; I Gusti Ayu Putri Kartika; I Gede Sastra Winata; Piers Andreas Noak (CV. Syntax Corporation Indonesia, 2024)
Indonesia has legalized abortion under certain conditions, such as pregnancy resulting from rape, through Government Regulation No. 28/2004. This policy has sparked heated debate because it contradicts the principle of protecting the right to life of the fetus. This study aims to provide a complex overview of the issue of abortion in Indonesia and its implications for human rights. The method used is normative legal research. This research is conducted by examining library materials or secondary data. The two approaches used are a statutory approach related to the legal issue of abortion and a conceptual approach to examine the medical legal understanding of abortion due to rape. Cases of sexual violence and rape in Indonesia are still high. In 2023, Komnas Perempuan recorded 2,078 cases of sexual violence, of which 143 were rapes. Abortion, in this context, is often used as a solution to address unwanted pregnancies. This research shows that while Government Regulation No. 28 of 2024 provides legitimacy to abortion, it is still contrary to the right to life of the fetus guaranteed by law. While abortion is considered a violation of the right to life, this policy is also considered a protection for women victims of sexual violence. Despite arguments to protect women's rights, the right to life of the fetus as a non-derogable right should not be ignored. Therefore, there needs to be a review of this regulation to ensure that all human rights, including the right to life of the fetus, are optimally protected.